Active travel to school, BMI and participation in organised and non-organised physical activity among Portuguese adolescents - Maria Paula Santos (2009)
Objectives. To assess the relationship between participation in organised (OPA) and non-organised physical activity (NOPA), commuting to school and BMI. Methods. Questionnaire assessing participation in OPA, NOPA, and travel behavior submitted in spring 2006 to 721 Portuguese secondary school students. Active travellers walked or biked (AT). Passive travellers drove or took the bus (PT). Height and weight were measured. Results. AT was related to NOPA among boys (odds ratio (OR) = 1.8, p <= 0.05) but not among girls. AT was unrelated to OPA. BMI was weakly associated with OPA (boys: OR = 0.56, p <= 0.05; girls: OR = 0.54, p:! 0.05) and not with NOPA. Conclusion. After-school organised and non-organised physical activities do not predict active travelling to school among Portuguese adolescents.